Metode Menentukan Kebutuhan Armada Penjualan: Studi Kasus Cabang Jakarta dari LIGI Perusahaan Asuransi Umum di Indonesia - Djojo, Brata Wibawa; Charlie, Oey (Bina Nusantara University, 2011)
Many companies face a classic problem in sales peopleâs turn-over or under-target because of uncompeteny of sales people or highly unreasonable sales target. On the other side, management has a perception that the sales people they have are uncompetence and more recruitment for sales people is not reasonable with cost and budget. If the company can not determine the sales force size, it will make a bad culture and business would not run properly. Through this research, the simply formulation will be applied at Jakarta Branch of a general insurance company LIGI (JLIGI) to their sales force at the existing condition and including in 2011. The formulations that will be applied for JLIGI are using breakdown method, workload method, and incremental method. Those three methods have each advantage and disadvantage, whereas breakdown method is a simple and general method, workload method is a more structural method and incremental method needs cost and profitability analysis of the years.Â